Carbon Incorporation and Anion Dynamics as Synergistic Drivers for Ultrafast Diffusion in Superionic LiCB11H12 and NaCB11H12. Issue 15 (20th February 2018) - Dimitrievska, Mirjana; Shea, Patrick; Kweon, Kyoung E.; Bercx, Marnik; Varley, Joel B.; Tang, Wan Si; Skripov, Alexander V.; Stavila, Vitalie; Udovic, Terrence J.; Wood, Brandon C.
Abstract: The disordered phases of LiCB11 H12 and NaCB11 H12 possess superb superionic conductivities that make them suitable as solid electrolytes. In these materials, cation diffusion correlates with high orientational mobilities of the CB11 H12 − anions; however, the precise relationship has yet to be demonstrated. In this work, ab initio molecular dynamics and quasielastic neutron scattering are combined to probe anion reorientations and their mechanistic connection to cation mobility over a range of timescales and temperatures. It is found that anions do not rotate freely, but rather transition rapidly between orientations defined by the cation sublattice symmetry. The symmetry‐breaking carbon atom in CB11 H12 − also plays a critical role by perturbing the energy landscape along the instantaneous orientation of the anion dipole, which couples fluctuations in the cation probability density directly to the anion motion. Anion reorientation rates exceed 3 × 10 10 s −1, suggesting the underlying energy landscape fluctuates dynamically on diffusion‐relevant timescales. Furthermore, carbon is found to modify the orientational preferences of the anions and aid rotational mobility, creating additional symmetry incompatibilities that inhibit ordering. The results suggest that synergy between the anion reorientational dynamics and the carbon‐modified cation–anion interaction accounts for the higher ionic conductivity in CB11 H12 − salts compared with B12 H12 2− . Abstract : Anion dynamics in the superionic solid electrolytes LiCB11 H12 and NaCB11 H12 are probed by combining ab initio molecular dynamics with quasielastic neutron scattering. It is shown how carbon strengthens the coupling between anion dynamics and local cation mobility to enhance ionic conductivity.